Contrasting patterns of phylogenetic diversity and alpine specialization across the alpine flora of the American mountain range system ... - Figueroa, Hector Fox; Marx, Hannah E.; De Souza Cortez, Maria Beatriz; Grady, Charles J.; Engle-Wrye, Nicholas; Beach, Jim; Stewart, Aimee; Folk, Ryan A.; Soltis, Douglas E.; Soltis, Pamela S.; Smith, Stephen A. (Dryad, 2021)
Although mountainous habitats contribute substantially to global biodiversity, comparatively little is known about biogeographic patterns of distributions of alpine species across multiple mountain ranges. Here, we present a detailed analysis of the distributions and phylogenetic affinities of alpine seed plant lineages across North, Central, and South American mountain systems. Using a comprehensive dataset that characterized the elevational niches of American seed plants in a continuously valued way, we were able to quantitatively investigate how the proportion of alpine habitat occupied by plants related to their biogeographic distributions at a regional scale and place these results in a phylogenetic context. We found alpine species diversity to be greatest in the central Andes and western North America, and that sites with lower phylogenetic diversity contained species with a greater degree of alpine specialization. In particular, near Arctic/ boreal alpine communities were characterized by low ... : File Descriptions: "alpine_taxonomy_v9.csv" This CSV file lists all 2397 alpine species in our dataset. "strategy" column indicates if this species was classified as Alpine Specialist (AS), or Alpine Generalist (AG), with subcategories of primarily montane (MN) or primarily lowland (LW) for generalists based on the majority of their non-alpine range. "specialization" column indicates whether that genus contains only specialists, generalists, or both. "SUPPLEMENTAL FIGURES AND TABLES" Contains a copy of the supplemental figures and tables referred to in the main text. "mountain_composition" This folder contains alpine species lists for each mountain or mountain range in the Americas, as defined by the Global Mountain Biodiversity Assessment (GMBA). ...